A pesca caiçara anterior ao surgimento da Barra Nova na Ilha do Cardoso, SP: subsídios à gestão pesqueira na região. - Tinoco, Idelmara de Alencar (Universidade Federal de São Carlos, 2023)
In the coast of the states of “São Paulo” and “Paraná” inhabit “caiçaras” communities, who base their livelihood and their income on artisanal fishing mainly. In the “Cananéia” region is located the “Ilha do Cardoso” State Park, a Conservation Unit in which traditional communities practice artisanal fishing in the estuarine and marine environment. The island underwent an erosion process in its southern portion that generated the opening of a new bar, which has affected the ecosystem and the local residents. In this context, this research presents information on the profile of “caiçara” fishing among communities close to the “Barra Nova” along the decade that preceded this event and proposes a preliminary prognosis of future consequences for local fishing. The fishing data analyzed came from the Fishing Activity Monitoring Program of the State of “São Paulo”, developed by the Fisheries Institute, and the information about the communities, description of the fishing gear, ecology and biology of the fish species were obtained from secondary sources. From the methodology employed, it was possible to obtain an overview of fishing over eleven years in the study area, making it possible to know the main products captured, and to understand the possible influence that “Barra Nova” can generate on the local fishing dynamics as well on the quality of life of the locals. The studies compiled on the ecology of the “manjuba-chata” show that juveniles of this species prefer areas with low salinity, which can change the logistic of this fishery due to the increase of salinity in the estuary. It is possible that fishing for other fish products does not change, due to their ecological behavior presenting interactions with marine and estuarine environments. However, the closure of the old bar became farther away and also more expensive the access to the coast by the fishers of the “Barra do Ararapira” and “Pontal do Leste” communities. Nevertheless, new studies involving the perception of the fishermen/residents in the region on the impacts generated by the opening of “Barra Nova” are still needed. The information presented herein will be able to help new research on the opening of “Barra Nova” and its consequences, as well contribute to decision-making about the fishing management in the area.
“Caiçara” fishing before the “Barra Nova” opening in the Cardoso Island, São Paulo: subsidies for fisheries management in the region.
Keywords: Pesca Artesanal; Erosão Costeira; População Tradicional; Ecologia Humana; Artisanal Fishing; Coastal Erosion; Traditional Population; Human Ecology; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA::RECURSOS PESQUEIROS MARINHOS; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA::RECURSOS PESQUEIROS MARINHOS::MANEJO E CONSERVACAO DE RECURSOS PESQUEIROS MARINHOS